Response of Planting Spatial and PGPR (Plant Growth Promoting Rhizobacteria) Concentration of Bamboo Roots on The Growth and Yield of Sweet Corn: Respon Jarak Tanam dan Konsentrasi PGPR (Plant Growth Prommoting Rhizobacteria) Akar Bambu Terhadap Pertumbuhan dan Hasil Tanaman Jagung Manis - Tangguh Prakoso; Heny Alpandari; Abdullah Alfalakhi (Universitas Muhammadiyah Sidoarjo, 2026)
The productivity of sweet corn must be continuously improved to meet increasing market demand. Inorganic fertilizers may reduce soil fertility. The application of (PGPR) derived from bamboo roots, which function as biofertilizers and biostimulants by enhancing nutrient availability and stimulating plant growth. Appropriate plant spacing is also an important agronomic practice for optimizing the use of light, water, nutrients, and growing space. This study aimed to evaluate the interaction between plant spacing and bamboo root PGPR concentration on the growth and yield of sweet corn. The experiment was conducted in Potroyudan Village, Jepara from December 2024 to March 2025 using a two-factor Randomized Complete Block Design (RCBD). The first factor consisted of three plant spacings (75 × 40 cm, 75 × 30 cm, and 75 × 20 cm), while the second factor included three PGPR concentrations (0, 25, and 50 ml L⁻¹). Data were analyzed using analysis of variance (ANOVA) followed by Duncan's Multiple Range Test (DMRT) at the 5% significance level. The interaction between plant spacing and PGPR concentration significantly affected plant height only at 6 weeks after planting. Plant spacing significantly influenced stem diameter, cob weight with husk, and cob length without husk. The 75 × 40 cm spacing produced the highest cob weight (276.48 g) and longest cob length (19.44 cm). PGPR concentration showed no significant effect, although 25 ml L⁻¹ tended to produce better growth and yield. Overall, plant spacing contributed more to sweet corn productivity than bamboo root PGPR under the conditions of this study.